Keanekaragaman Jamur Makro di Kawasan Hutan Mangrove Teluk Buo Bungus Teluk Kabung Sumatera Barat - Anisa Asri; Dezi Handayani (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
Indonesia is the center of the world's biodiversity known as a megabiodiversity country. One area that has a high biodiversity is mangrove forests. The biodiversity found in mangrove forests is fungi. The purpose of this study is to find out what types of macro mushrooms are found in the Mangrove Forest Area of Buo Bungus Teluk Kabung West Sumatra. This type of research is descriptive, the time and place of this study was conducted in August-December 2021 in the Mangrove Forest Area of Teluk Buo Bungus Teluk Kabung West Sumatra. The method used is a direct survey into the field. Based on the research that has been done, the results obtained are 11 species of macro fungi that are mostly of the Agaricomycetes class. Based on the results of the study it can be concluded that macro mushrooms obtained are Trametes sanguinea, Trametes sp 1, T. sp 2, Polyporus leptochepalus, P. sp 1, Ganoderma sp 1, G. sp 2, Daedaleopsis sp, Schizophyllum commune, Pleurotus ostreatus, dan Auricularia angiospermum. The genus most commonly found is the genus Polyporaceae as many 5 species.